The Influence Of Growth Opportunity And Return On Equity (ROE) Toward Company Capital Structure - Hamdan Hamdan (Yayasan Ilomata, 2020)
This study aims to determine the effect of growth opportunity and return on equity the capital structure of the automotive sub-sector companies and components listed on the Indonesia Stock Exchange (IDX) in 2014-2018. The sample used in this study is the automotive sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018. The sampling technique used was purposive sampling method and obtained 8 companies. The data collected is secondary data with the method of documentation through www.idx.com in the form of a company annual report. The analytical tool used for hypothesis testing is SPPS 20. The results of this study are (1) Growth opportunity does not have a significant effect on the company's capital structure. (2) Return on equity has a significant effect on the company's capital structure.